1997
DOI: 10.1111/1467-8381.00030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trade Liberalization on Taiwan: A Computable General Equilibrium Analysis

Abstract: Joining the GATT has been established as one of the most important economic and political targets of the Taiwan government. However, the effects of this action are difficult to establish. Because of the openness of Taiwan's domestic market there could be serious changes in the production structure and income distribution, especially in the relative status of the agricultural and nonagricultural sectors, of protected and unprotected sectors, and also of producers and consumers. The possible high cost of this mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Chou and others (1997) applied CGE simulations to assess the impact of tariff liberalization under trade agreements on the Taiwanese economy. Their findings suggested that such liberalization within trade agreements is beneficial, leading to increased real GDP, consumption, and welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chou and others (1997) applied CGE simulations to assess the impact of tariff liberalization under trade agreements on the Taiwanese economy. Their findings suggested that such liberalization within trade agreements is beneficial, leading to increased real GDP, consumption, and welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Having undergone rapid export-led postwar development, both economies liberalized service FDI amid mounting pressures from the West during the 1980s to reduce trade surplus. Following the Uruguay round of the General Agreement on Tariffs and Trade negotiations, which covered trade in services 4 and the United States Trade Representative’s adoption of Super 301, a measure to improve U.S. trade worldwide, 5 Taiwan reduced its import duty from 10.49% in 1981 to 6.74% in 1992 and revised its tariff schedule eight times (Chou et al., 1997). Korea also reduced its operative import tariff to 5.6% by 1985 from 8% in 1970, in addition to drastically reducing categories of goods that were formally banned or regulated by import quotas (Nam, 1995).…”
Section: Variations In East Asia: Exploring the Contextmentioning
confidence: 99%
“…In Taiwan, while there are some discussions on the impact of liberalization, few related specifically to the effects of martial law on the economy. Chou, et al (1997) applied single country computable general equilibrium model to assess the effects of trade liberalization (in their case, joining GATT) on Taiwan. They showed that, from 1971 to 1986, and to 1992, the average tariff rate in Taiwan was reduced from 12.25% to 6.96%, and to 4.87%; the import duty rate was also reduced from 13.51% to 9.31%, and to 6.74%.…”
Section: Some Previous Studies On the Impact Of Liberalizationmentioning
confidence: 99%